A new approach based on fuzzy logic technique for determination of packet priority - Tuncer, T; Tatar, Y (Dynamic Publishers, 2002)
In this paper, we propose a novel method using fuzzy logic technique to determine the packet priority in packet switching networks. The developed fuzzy system uses four inputs. These are packet's Time-to-Live (TTL), waiting time in the line of packet, sequence number of packets in the line and packet size. By the help of these inputs, value of packet's priority is computed. However, to overcome disadvantage of FIFO and according to packet size priority determining algorithms is considered both waiting time of packet and packet's TTL. Experimental results show the effectiveness and applicability of the proposed method.
2nd International Conference on Neural, Parallel, and Scientific Computations -- AUG 07-10, 2002 -- MOREHOUSE COLL, ATLANTA, GA